Dermatology - Braun-Falco, Otto; Plewig, Gerd; Wolff, Helmut H.; Winkelmann, Richard K. (Springer Berlin Heidelberg, 1991)
"Dermatology" covers all the classical and related fields of dermatology, providing a wealth of infor- mation on clinical features, pathophysiology, and differen- tial diagnosis. Approximately 850 excellent color figures help the reader become acquainted with the immense variety of dermatological diseases. Each chapter contains detailed proposals for comprehensive therapy. The book is a must for every doctor confronted with dermatological problems